THE LIVING QUR'AN: POTRET BUDAYA TAHFIZ AL-QUR'AN DI NUSANTARA - Atabik, Ahmad (LP2M IAIN kUDUS, 2014)
The Living Qur’an: nusanTara Qur’an Tahfiz cuLTure porTraiT. The study of the living Qur’an is the study of a variety of social events related to the presence of the Qur’an or the existence of the Qur’an in certain a Moslem community. Based on it, it will seem the social response (reality) of the Moslem community to make a living and turn on the Qur’an through a continuous interaction. The living Qur’an actually originated from the Qur’an phenomena in everyday life, that is, the meaning and function of the Qur’an that real are understood and experienced by the Moslem community. among the living Qur’an found on the archipelago’s Moslem community is culturally or memorize (tahfiz) of the Qur’an. This tradition is one of the many phenomenon of Moslem in turn or present the Qur’an in everyday life by means of read through it entirely. This tradition is widespread in some indonesian islamic community, especially among the students of boarding school (santri), as a result it form an entity of local culture.